MGMT promoter methylation in malignant gliomas: ready for personalized medicine? - Weller, Michael; Stupp, Roger; Reifenberger, Guido; Brandes, Alba A.; Van den Bent, Martin J.; Wick, Wolfgang; Hegi, Monika E. (Nature reviews. Neurology, 2010)
The DNA repair enzymeO6-methylguanine-DNA methyltransferase (MGMT) antagonizes the effects of alkylating agents, and its expression is associated with resistance to cancer therapy based on these compounds. Weller et al. consider the prognostic and predictive value of MGMT gene silencing in gliomas and describe the assays that are commonly used to evaluate MGMT status, focusing particularly on MGMT promoter methylation, which is the key mechanism of MGMTgene silencing.